Autophagy and mitochondrial dynamics contribute to the protective effect of diosgenin against 3-MCPD induced kidney injury. (1st March 2022) - Zhong, Yujie; Sun, Dianjun; Yao, Yanpeng; Liu, Qi; Guo, Tianmin; Wang, Xin; Peng, Xiaoli
Abstract: 3-Chloro-1, 2-propanediol (3-MCPD) is a widespread food contaminant with kidney as the main target organ. The exploration of ingredients as intervention strategy towards 3-MCPD induced nephrotoxicity is needed. Diosgenin (DIO) is a steroidal saponin presented in several plants and foods. Here we assessed whether DIO attenuates nephrotoxicity induced by 3-MCPD using Human embryonic kidney 293 (HEK293) cells and Sprague-Dawley (SD) rats. The results showed that DIO (2, 6, 8 μM) increased cell viability and exerted inhibitory effect on caspase 3 and caspase 9 activities. Histological examination of rats showed that 15 mg/kg bw DIO ameliorated renal pathological changes caused by 3-MCPD (30 mg/kg bw). DIO also induced autophagy and the blockade of autophagy with 3-Methyladenine (3-MA) aggravated mitochondrial apoptosis induced by 3-MCPD in HEK293 cells. Moreover, treatment with DIO caused an increase in p-LKB1/LKB1 and p-AMPK/AMPK expressions and a decrease in p-mTOR/mTOR, p-ULK1(Ser 757 ), p-P70S6K and p-4EBP1 expressions. Additionally, DIO improved mitochondrial dynamics mainly through inhibiting the relocation of DRP1 on mitochondria and enhancing MFN1 and MFN2 expressions. In conclusion, our study demonstrated for the first time that DIO protected against kidney injury induced by 3-MCPD through the induction of autophagy via LKB1-AMPK-mTOR pathway and the improvement of mitochondrial fission and fusion. Graphical abstract: Image 1 Highlights: Diosgenin alleviated nephrotoxicity induced by 3-MCPD in vivo and in vitro. Autophagy induction contributes to the protective effect of diosgenin against 3-MCPD-induced kidney injury. The improvement of mitochondrial dynamics by diosgenin protected against 3-MCPD-induced kidney injury.